Implementation of Science Learning Based on Higher Order Thinking Skills (HOTS) in Elementary Schools - Abdul Gofur, Muhamad; ., Andriyansyah; Hanifah, Umi (El Banar : Jurnal Pendidikan dan Pengajaran, 2025)
This study aims to describe the implementation of Science learning based on Higher Order Thinking Skills (HOTS) in grades I and IV at SDIT Al Insan Islamic School, Bekasi City. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation. The results show that teachers have designed and implemented HOTS-oriented lesson plans, despite facing constraints such as limited resources and varying levels of student understanding. The solutions applied include teacher training and contextual learning approaches. This study concludes that HOTS-based learning enhances students' critical and analytical thinking skills, although several challenges remain in its implementation.